Atrial Fibrillation With Rapid Ventricular Response in Pregnancy - Chia-Hui Lin; Chien-Nan Lee (Elsevier, 2008)
Objective: To report a case of atrial fibrillation with rapid ventricular response occurring during pregnancy. Case Report: A 35-year-old woman, gravida 3, para 1, abortus 1, with a history of persistent supraventricular arrhythmia, presented at 22 weeks' gestation. After adenosine administration, electrocardiography revealed atrial fibrillation with rapid ventricular response. The episode was complicated by hemodynamic instability and was refractory to verapamil. Sinus rhythm was restored after synchronized electrical cardioversion under sedation. Sotalol (80 mg) was given for arrhythmia and to control heart rate. The patient experienced a second episode of supraventricular arrhythmia at 26 weeks' gestation, which was also reversed after cardioversion. She delivered a healthy male baby at 38 weeks' gestation via scheduled cesarean section. Conclusion: Arrhythmias with underlying heart disease can result in serious hemodynamic deterioration. Electrical cardioversion is well-tolerated and effective in pregnant women and should not be withheld if clinically indicated.